Evaluating Islamic Marketing Strategy of Hajj-Umrah Travel in Digital Era: Mengevaluasi Strategi Pemasaran Syariah Travel Haji-Umrah di Era Digital - Dihliza Basya; Maziyah Mazza Basya (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Hajj and Umrah travel sector is facing intense competition with the rise of licensed and unlicensed travel providers. Specific Background: In the digital era, social media platforms play a crucial role in marketing strategies to attract prospective pilgrims, but these efforts must remain aligned with Islamic ethical principles. Knowledge Gap: Despite growing digitalization, there is limited evaluation of how Islamic marketing strategies are implemented and assessed using structured analytical tools. Aims: This study aims to evaluate the Islamic marketing strategy applied by a pesantren-based Hajj and Umrah travel company through the SERVO (Strategy, Environment, Resources, Values, Organization) framework. Results: Using qualitative methods—interviews, observations, and documentation—the study finds that while digital marketing has improved customer engagement and booking conversions, the company still needs to enhance service response, transparency, and strategic competitiveness. Novelty: The integration of SERVO analysis with Islamic values offers a unique approach to assess strategic fit in faith-based service industries. Implications: The findings highlight the importance of aligning digital strategies with Islamic marketing ethics and strategic responsiveness to ensure sustainable performance and trust in religious travel services.Highlight : The study evaluates Islamic marketing strategies in hajj and umrah travel using SERVO analysis to improve competitiveness in the digital era. Findings highlight the importance of optimizing social media, improving service response, and ensuring ethical alignment with sharia principles. Adjustments to commission fees and target pilgrims are needed to support sustainable business growth. Keywords : Digitalization, Hajj and Umrah Travel, Islamic Marketing Strategy, SERVO Analysis, Digital Marketing